Product Characterization and Marketing Strategy of â€œBREM UNGUâ€: Rejuvenation of Indonesian Traditional Food with Local Purple Sweet Potato as the Source of Natural Colorant - Jatiyati, Greta; Jessica, Benedieta Prytania; Indrawati, Renny (Indonesian Journal of Natural Pigments, 2021)
Solid brem is an indigenous fermented food of Indonesia, which often has typical form of long thick bar, white to yellow in color, sweet-sour taste with cooling sensation, and it is easy to crumble by the presence of water. These unique characteristics are generated through alcoholic fermentation of glutinous rice, followed by filtration, concentration, whipping and dehydration. Although it is continuously produced and sold as regional specialties of Madiun, East Java, most people refuse to consume this solid brem due to its high sugar content and lack of information that describes its potential health benefits. The present study is attempting the possibility of combining glutinous rice with another local material having well-known health benefit. Here, we utilize the potency of local purple sweet potato (Ipomoea batatas var. Gunung Kawi), being rich in carbohydrate and anthocyanines, to partly substitute the glutinous rice while adding the health benefits of the final product. The present anthocyanins in sweet potato has been well-studied, exhibiting antioxidant, anti-inflammation, and hepatoprotective activities. The raw materials were subjected to yeast fermentation for 7 days, and subsequently extracted using manual mechanical press. A series of materials ratio (extract of fermented glutinous rice: purple sweet potato = 30:1, 15:1, 15:2) was determined prior to dehydration of brem, and then the color, sugar content, pH, antioxidant activity, and sensory properties of the resulted product were analyzed. Moreover, the competitive analysis and marketing strategy will also be discussed in order to make sure the sustainability of this new innovation.